Pengaruh Kepercayaan Diri terhadap Kematangan Karir Siswa SMK di Kota Cimahi - Annisa Komarawati Waluya; Temi Damayanti Djamhoer (UNISBA Press, 2022)
Abstract. One of the developmental tasks of adolescence is to be able to plan a future career. Individuals can be said to be mature in their careers if they are ready to make career decisions. One of the factors that can increase career maturity is self-confidence in individuals. With the presence of self-confidence can affect the success of students in learning and working. The purpose of this study was to examine the effect of self-confidence on career maturity of vocational students in Cimahi City. This type of causality research with a quantitative approach. The research subjects were 400 SMK students in Cimahi City. The measuring instrument of this research uses a self-confidence scale which refers to Lauster's theory and a career maturity scale of Nurul Sri and Dewi Sartika which refers to the Super theory. Data analysis using simple regression test. The results of data analysis show that H1 is accepted because the significance value is 0.000 <0.05 so it can be concluded that there is an influence of self-confidence on career maturity with an R Square value of 0.180, meaning that self-confidence has an effect of 18% on career maturity of SMK students in Cimahi City. Abstrak. Salah satu tugas perkembangan masa remaja adalah mampu merencanakan karir masa depannya. Individu dapat dikatakan matang karirnya jika individu siap dalam mengambil keputusan karirnya. Salah satu faktor yang dapat meningkatkan kematangan karir adalah adanya kepercayaan diri pada individu. Dengan adanya kepercayaan diri dapat mempengaruhi keberhasilan siswa dalam belajar dan bekerja. Tujuan penelitian ini untuk menguji pengaruh kepercayaan diri terhadap kematangan karir siswa SMK di Kota Cimahi. Jenis penelitian kausalitas dengan pendekatan kuantitatif. Subjek penelitian 400 siswa SMK di Kota Cimahi. Alat ukur penelitian menggunakan skala kepercayaan diri yang mengacu pada teori Lauster dan skala kematangan karir Nurul Sri dan Dewi Sartika yang mengacu pada teori Super. Analisis data menggunakan uji regresi sederhana. Hasil analisis data menunjukkan bahwa H1 diterima karena nilai signifikansi 0,000 < 0,05 sehingga disimpulkan terdapat pengaruh kepercayaan diri terhadap kematangan karir dengan nilai R Square sebesar 0,180, artinya kepercayaan diri berpengaruh 18% terhadap kematangan karir siswa SMK di Kota Cimahi.